Group Merger Between Political Parties: The Role of the Ingroup Projection Process. Issue 1 (24th October 2012) - Sacchi, Simona; Carnaghi, Andrea; Castellini, Federica; Colombo, Monica
<x xml:space="preserve">Abstract</x> In 2007, the two most important Italian left‐wing parties merged into a single political entity. This study intends to analyze the merging process. Specifically, and in line with the ingroup projection hypothesis of Mummendey & Wenzel, we have explored whether the identification and the favoritism toward the upcoming common group was affected by the perceivers' projection of specific and common stereotypical traits from the subordinate groups to the superordinate one. Political militants' (N = 132) levels of ingroup identification; their representations of the previous ingroup, outgroup, and of the new party; and their attitudes towards the common group were assessed. Results confirmed that the cognitive representation of the merged party was shaped much more on the basis of the typical traits of the ingroup than of the outgroup. Moreover, structural equation analyses showed that the identification with the superordinate category and the consequent favoritism toward the merger were related to the projection of ingroup attributes. The findings also suggested that the ingroup projection may be particularly crucial when the intergroup bias is high. Finally, political implications are discussed in terms of obstacles and resources inherent to the merging process.